SUNAT- SUNAT SHALAT DARI RAKAAT KEDUA SAMPAI SALAM - Husni Husni; Irwan Irwan (STIS Nahdlatul Ulama Aceh, 2020)
In the implementation of prayer, for example, it is often found that there are many differences, both in terms of the procedure and the determination of the pillars and circumcision. For example, such as the implementation of the dawn prayer, there are groups who say qunut is circumcision, some do not recommend it on the grounds that it is categorized as permissible work. The purpose of this paper is to find out what causes these differences and what is the basis or the evidence for each opinion. This study says that qunut in the morning prayer according to the Shafi'i school in the dawn prayer after bowing from the second raka'at is circumcision. Meanwhile, Sayid Sabiq concluded that qunut is something permissible. Read sholawat on the prophet. After the final tasyahhud, according to Sayyid Sabiq, he thought this was circumcision. Meanwhile, according to Zainuddin al-Malibary, he is of the opinion that it is mandatory. The only thing they have in common here is the matter of praying to the Prophet's family.